Adjuvanted recombinant zoster vaccine in adult autologous stem cell transplant recipients: polyfunctional immune responses and lessons for clinical practice. Issue 11 (2nd November 2021) - Stadtmauer, Edward A.; Sullivan, Keith M.; El Idrissi, Mohamed; Salaun, Bruno; Alonso Alonso, Aránzazu; Andreadis, Charalambos; Anttila, Veli-Jukka; Bloor, Adrian JC; Broady, Raewyn; Cellini, Claudia; Cuneo, Antonio; Dagnew, Alemnew F.; et al.
ABSTRACT: Immunocompromised individuals, particularly autologous hematopoietic stem cell transplant (auHSCT) recipients, are at high risk for herpes zoster (HZ). We provide an in-depth description of humoral and cell-mediated immune (CMI) responses by age (protocol-defined) or underlying disease (post-hoc) as well as efficacy by underlying disease (post-hoc) of the adjuvanted recombinant zoster vaccine (RZV) in a randomized observer-blind phase III trial (ZOE-HSCT, NCT01610414). 1846 adult auHSCT recipients were randomized to receive a first dose of either RZV or placebo 50–70 days post-auHSCT, followed by the second dose at 1–2 months (M) later. In cohorts of 114–1721 participants, at 1 M post-second vaccine dose: Anti-gE antibody geometric mean concentrations (GMCs) and median gE-specific CD4[2+] T-cell frequencies (CD4 T cells expressing ≥2 of four assessed activation markers) were similar between 18–49 and ≥50-year-olds. Despite lower anti-gE antibody GMCs in non-Hodgkin B-cell lymphoma (NHBCL) patients, CD4[2+] T-cell frequencies were similar between NHBCL and other underlying diseases. The proportion of polyfunctional CD4 T cells increased over time, accounting for 79.6% of gE-specific CD4 T cells at 24 M post-dose two. Vaccine efficacy against HZ ranged between 42.5% and 82.5% across underlying diseases and was statistically significant in NHBCL and multiple myeloma patients. In conclusion, two RZV doses administered early post-auHSCT induced robust, persistent, and polyfunctional gE-specific immune responses. Efficacy against HZ was also high in NHBCL patients despite the lower humoral response. PLAIN LANGUAGE SUMMARY: What is the context? After haematopoietic stem cell transplantation, patients have impaired immunity from conditioning chemotherapy regimens, often exacerbated by underlying diseases, putting them at high risk of developing herpes zoster. In this population, antiviral prophylaxis is the current standard of care to reduce herpes zoster risk. Vaccination provides an additional means to prevent herpes zoster. Live-attenuated vaccines are generally contraindicated in immunocompromised patients. A non-live, adjuvanted recombinant zoster vaccine (RZV, Shingrix, GSK), has been approved for use in adults ≥50 years of age in the European Union, United States, Canada, Australia, Japan, and China. This vaccine is highly efficacious at preventing herpes zoster in adults over 50 years of age, as demonstrated in large, placebo-controlled randomised trials. Importantly, Shingrix use is not contraindicated in immunocompromised conditions, and was found to be highly efficacious in adults who had recently undergone autologous haematopoietic stem cell transplant. What is new? In autologous haematopoietic stem cell transplant recipients in whom Shingrix has demonstrated efficacy, two doses elicited high and persistent immune responses. Date presented here further support our understanding of the impact of specific factors such as age or underlying diseases on the vaccine's effect in the population studied, as well as the characteristics of the elicited cell-mediated immune responses. What is the impact? These results indicate that Shingrix, given shortly after haematopoietic stem cell transplant, can induce robust immune responses and reduce the risk of herpes zoster, even in individuals with immunosuppression due to underlying disease and/or use of immunosuppressive therapies, regardless of age or underlying disease.